Pengaruh Goji Berry (Lycium barbarum) Terhadap Kadar Glukosa Darah Puasa Dan Dua Jam Postprandial Pria Dewasa Normoglikemik - Yenny Frida Setiawan; Fenny Fenny; Heddy Herdiman; Willie Japaries; Suminah Suminah (Institut Nalanda, 2023)
Background: Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to abnormal insulin secretion, insulin function or both. Based on World Health Organization, DM was the eighth leading cause of death in the world (2012), 43% of deaths happened at age less than 70 years. Microvascular and macrovascular complications caused by DM, long-term therapy, and side effects of therapy have greatly affected the patients’ quality of life. Hence, people have seeked many DM adjuvant therapy from herbs, one of which is goji berries [Lycium barbarum]. The Lycium barbarum polysaccharides (LBP) has been shown to have blood glucose lowering effect. Methods: This study aimed to investigate the effect of goji berries on reducing blood glucose levels. The research was conducted through pre and posttest design on fasting and two hours postprandial blood glucose levels in young adult males before and after receiving 20 g dried goji berries per day for 14 days. Statistical analysis used in this research was paired t test with α=0.05. Results: This study showed that the consumption of goji berries for 14 days did not significantly affect the fasting and two hours postprandial blood glucose levels (p>0.05) of the volunteers. Conclusion: Goji berries did not reduce fasting and two hours postprandial blood glucose levels in normoglycemic males.